Method for selectively leaching lithium from waste lithium iron phosphate battery and application
By treating the positive electrode material of waste lithium iron phosphate batteries in brine and alkali solutions, and using gas micro-nano bubbles for selective leaching in the acid solution, the problems of lithium loss and performance degradation in the existing recycling methods are solved, and high efficiency is achieved , environmentally friendly lithium recycling, suitable for large-scale industrial production.
Patent Information
- Application Number
- CN202411299450.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-14
AI Technical Summary
In the existing waste lithium iron phosphate battery recycling methods, ignition recycling leads to a degradation of the performance of the positive electrode material, and wet recycling uses a large number of acids and oxidants, resulting in lithium loss and heteroatom introduction, and the process is complex and the pollution problem is serious.
After discharge and dismantling in brine, the positive electrode material is placed in alkali solution and ultrasonic treatment is carried out. Then, gas micro-nano bubbles are used in the acid solution to leaching lithium to achieve selective leaching, reducing the loss of lithium and iron, and improving recovery rate. .
It realizes the efficient recovery rate of lithium elements, controls the leaching rate of iron, forms a closed-circuit process, avoids secondary pollution, is suitable for industrial production, and reduces production costs.
Smart Images

Figure CN119307721A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium recovery, and in particular relates to a method and application of selectively leaching lithium from waste lithium iron phosphate batteries. Background Art
[0002] With the development of technology, lithium batteries are widely used in the fields of new energy vehicles, energy storage power stations, 3C products and other industries. Lithium-ion batteries are chosen by more automobile manufacturers due to their high capacity and relatively stable cycle performance, especially the wide source of lithium iron phosphate materials, good thermal stability, high safety performance and low price. Generally, the service life of lithium batteries is 5-7 years. After reaching the end of their service life, more and more waste lithium batteries will be generated. If not treated, the pollutants such as electrolyte, organic matter, adhesives contained in waste lithium iron phosphate batteries will cause serious pollution to water resources and soil. At the same time, lithium iron phosphate batteries contain a large amount of lithium resources. Recycling them can not only protect the environment, but also alleviate the shortage of lithium resources and obtain economic benefits.
[0003] The current recycling methods for waste lithium iron phosphate battery positive electrode materials mainly include pyrometallurgical recycling and wet recycling. Pyrometallurgical recycling is to remove the binder and conductive agent by crushing and calcining the positive electrode materials obtained after discharging and disassembling the waste lithium iron phosphate batteries. This method is to roast the positive electrode materials obtained after disassembly under inert atmosphere conditions. This method can carbonize the binder and conductive agent in the positive electrode material and increase the carbon content of the positive electrode material. Too high carbon content in the positive electrode material will lead to a decrease in energy density. At the same time, the positive electrode binder usually contains impurity elements such as nitrogen and fluorine, which are carbonized to obtain impurity carbon, and the conductivity cannot meet the requirements of the positive electrode conductive agent, thereby resulting in a decrease in the electronic conductivity of the recycled lithium iron phosphate positive electrode material, an increase in the internal resistance of the battery, and an impact on the rate performance of the battery. At the same time, the pyrometallurgical treatment process inevitably produces a large amount of waste gas and other problems. Wet recycling is to discharge the waste lithium iron phosphate battery first, then disassemble the positive electrode active material, add oxidant and acid to selectively extract lithium or extract lithium and iron at the same time and then precipitate in steps to obtain the corresponding product or add lithium iron phosphate positive electrode active material. The above-mentioned wet recycling method is used to prepare waste lithium iron phosphate positive electrode materials into battery-grade lithium carbonate, iron phosphate and other products. From the perspective of recycling, a large amount of acid and alkali is used to achieve the recycling and reuse of valuable metals. Not only is the recycling process complicated, but a large amount of acid and alkali wastewater will be generated, which is not conducive to subsequent treatment.
[0004] The existing conventional methods for recovering positive electrode materials are prone to lithium loss, low lithium recovery rate, low oxidant utilization rate, and easy introduction of heteroatoms. Summary of the invention
[0005] In view of the problems that the existing wet recovery process of waste lithium iron phosphate uses a large amount of acid and oxidant with low utilization rate, and the fire recovery process has the problem of decreased performance of positive electrode materials after recovery, the primary purpose of the present invention is to provide a method for selectively leaching lithium from waste lithium iron phosphate batteries.
[0006] Another object of the present invention is to provide an application of the above method for selectively leaching lithium from waste lithium iron phosphate batteries.
[0007] The object of the present invention is achieved by the following technical solution: A method for selectively leaching lithium from waste lithium iron phosphate batteries, comprising the following steps:
[0008] (1) discharging the waste lithium iron phosphate battery in salt water, crushing and disassembling the battery to obtain lithium iron phosphate material, and separating the positive electrode material; placing the obtained positive electrode material in an alkaline solution for ultrasonication, separation, and drying to obtain a cathode material to be treated;
[0009] (2) placing the cathode material obtained in step (1) in an acid solution, leaching with gas micro-nano bubbles, and filtering to obtain a lithium-rich leaching solution.
[0010] In step (1):
[0011] The brine is preferably a NaCl solution with a concentration of 5-10% by mass; more preferably a NaCl solution with a concentration of 8% by mass.
[0012] The degree of discharge is preferably to discharge to below 0.2V.
[0013] The alkaline solution is preferably a NaOH solution with a concentration of 0.2-0.5M (M is the abbreviation of mol / L); more preferably a NaOH solution with a concentration of 0.3M.
[0014] The amount of the alkaline solution is preferably calculated based on a ratio of 1 g of positive electrode material to the alkaline solution of 5 to 15 mL; more preferably, the ratio of 1 g of positive electrode material to the alkaline solution is calculated based on a ratio of 1 g of positive electrode material to the alkaline solution of 10 mL.
[0015] The ultrasonic conditions are preferably: 35-45kHz, 400-600W; more preferably: 40kHz, 500W.
[0016] The ultrasonic time is preferably 10 to 30 minutes.
[0017] The drying conditions are preferably 60°C to 120°C for 6 to 24 hours; more preferably 80°C to 120°C for 12 to 24 hours.
[0018] In step (2):
[0019] The concentration of the acid solution is preferably 0.01 to 0.04 mol / L; more preferably 0.01 to 0.025 mol / L.
[0020] The amount of the acid solution is preferably calculated based on a ratio of 5 to 100 g:1 L of cathode material to acid solution; more preferably, the ratio of 5 to 10 g:1 L of cathode material to acid solution.
[0021] The acid is at least one of H2SO4, HCl, citric acid, phosphoric acid, oxalic acid and acetic acid; preferably H2SO4.
[0022] The gas is preferably at least one of O3, O2 and air; preferably O3.
[0023] The gas flow rate during the leaching is 80-120 mL / min, preferably 100 mL / min.
[0024] When the gas is O3, the O3 concentration is 80-100 mg / L, preferably 90 mg / L.
[0025] The diameter of the micro-nano bubbles is preferably 10-130 nm.
[0026] The conditions for generating the micro-nano bubbles are preferably an air flow rate of 80-120 mL and a power of 380 W.
[0027] The leaching time is preferably 10 to 150 minutes, and more preferably 30 to 60 minutes.
[0028] The leaching temperature is 10-80°C, preferably room temperature.
[0029] The room temperature is 10-40°C, preferably 20-30°C.
[0030] The above method for selectively leaching lithium from waste lithium iron phosphate batteries has a high leaching rate for lithium elements, controls the leaching rate of iron, and is beneficial for recovering lithium elements; thus, it is suitable for recovering high-purity lithium.
[0031] Compared with the prior art, the present invention has the following advantages and effects:
[0032] The present invention is suitable for forming a closed-circuit process, will not generate secondary pollution, takes into account both environmental protection and economic benefits, has a simple process, and has a low production cost, and is suitable for large-scale industrial production.
[0033] The invention can achieve a lithium leaching rate of 100% for waste lithium iron phosphate batteries, and a iron leaching rate that can be controlled to be above 1%, and can reach a maximum of 0.11%. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1This is a schematic diagram of lithium recovery by ozone micro-nano bubble leaching. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0036] Example 1
[0037] Waste lithium iron phosphate batteries (purchased on the market) were immersed in a NaCl solution with a mass fraction of 8% and discharged until the voltage was below 0.2V, which took about 48 hours, and the positive electrode material was disassembled. The obtained positive electrode material was ultrasonically treated (40kHz, 500W) for 20 minutes in a NaOH solution with a concentration of 0.3M, wherein the positive electrode material and the NaOH solution were added at a solid-liquid ratio of 1g:10mL, and the positive electrode material fell off the aluminum foil, dried at 80°C for 12 hours, and ground to obtain the cathode powder to be treated.
[0038] Take 10g of the cathode powder obtained by treatment and 993.75mL of deionized water into a three-necked flask and mix them evenly, add 6.25mL of 4M dilute sulfuric acid solution, and then introduce ozone micro-nano bubbles for sufficient reaction. After filtering, lithium-rich leaching solution, iron phosphate and carbon slag are obtained; the selected ozone concentration is 90mg / L, the gas flow rate is 100mL / min, the temperature is room temperature, the leaching time is 30min, and the total volume of the leaching solution is 1L. Figure 1 As shown, ozone micro-nano bubbles are generated by an ozone generator and a micro-nano bubble generator, the air inlet flow rate of the micro-nano bubble generator is 80-120 mL, the power is 380 W, and the diameter of the generated micro-nano bubbles is 10-130 nm. The metal ion content of the leaching solution is measured by inductively coupled plasma emission spectrometer (ICP-OES), and the recovery of lithium and iron obtained by aqua regia digestion method (National Environmental Protection Standard of the People's Republic of China, HJ 803-2016) is used as a standard, and the recovery rate of lithium is calculated to be 100%, and the recovery rate of iron is 0.11%, as shown in Table 1.
[0039] Example 2
[0040] The waste lithium iron phosphate battery was immersed in a NaCl solution with a mass fraction of 8% and discharged until the voltage was below 0.2V, which took about 48 hours. The positive electrode material was disassembled and ultrasonicated (40kHz, 500W) in a NaOH solution with a concentration of 0.3M for 20 minutes, wherein the positive electrode material and the NaOH solution were added in a solid-liquid ratio of 1g:10mL. The positive electrode material fell off the aluminum foil, dried at 80°C for 12 hours, and ground to obtain the cathode powder to be treated.
[0041] 10g of the cathode powder obtained by the treatment is put into a three-necked flask and mixed with 990mL of deionized water, 10mL of a 4M dilute sulfuric acid solution is added, and then ozone micro-nano bubbles are introduced for sufficient reaction, and lithium-rich leaching solution, iron phosphate and carbon slag are obtained after filtration; the selected ozone concentration is 90mg / L, the gas flow rate is 100mL / min, the temperature is room temperature, the leaching time is 30min, and the total volume of the leaching solution is 1L. Ozone micro-nano bubbles are generated by an ozone generator and a micro-nano bubble generator, the air intake flow rate of the micro-nano bubble generator is 80-120mL, the power is 380W, and the diameter of the generated micro-nano bubbles is 10-130nm. The metal ion content of the leaching solution was measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The recovery of lithium and iron obtained by the aqua regia digestion method (National Environmental Protection Standard of the People's Republic of China, HJ 803-2016) was used as a standard, and the recovery rate of lithium was calculated to be 100% and the recovery rate of iron was 12%, as shown in Table 1.
[0042] Example 3
[0043] The waste lithium iron phosphate battery was immersed in a NaCl solution with a mass fraction of 8% and discharged until the voltage was below 0.2V, which took about 48 hours. The positive electrode material was disassembled and ultrasonicated (40kHz, 500W) in a NaOH solution with a concentration of 0.3M for 20 minutes, wherein the positive electrode material and the NaOH solution were added in a solid-liquid ratio of 1g:10mL. The positive electrode material fell off the aluminum foil, dried at 120°C for 6 hours, and ground to obtain the cathode powder to be treated.
[0044] 5g of the cathode powder obtained by the above treatment was put into a three-necked flask with 997.5mL of deionized water and mixed evenly, 2.5mL of a 4M dilute sulfuric acid solution was added, and then ozone micro-nano bubbles were introduced for sufficient reaction, and lithium-rich leachate, iron phosphate and carbon slag were obtained after filtration; the selected ozone concentration was 90mg / L, the gas flow rate was 100mL / min, the temperature was room temperature, the leaching time was 30min, and the total volume of the leachate was 1L. Ozone micro-nano bubbles were generated by an ozone generator and a micro-nano bubble generator, the air intake flow rate of the micro-nano bubble generator was 80-120mL, the power was 380W, and the diameter of the generated micro-nano bubbles was 10-130nm. The metal ion content of the leaching solution was measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The recovery of lithium and iron obtained by the aqua regia digestion method (National Environmental Protection Standard of the People's Republic of China, HJ 803-2016) was used as a standard, and the recovery rate of lithium was calculated to be 100% and the recovery rate of iron was 0.68%, as shown in Table 1.
[0045] Example 4
[0046] The waste lithium iron phosphate battery was immersed in a NaCl solution with a mass fraction of 8% and discharged until the voltage was below 0.2V, which took about 48 hours. The positive electrode material was disassembled and ultrasonicated (40kHz, 500W) in a NaOH solution with a concentration of 0.3M for 20 minutes, wherein the positive electrode material and the NaOH solution were added in a solid-liquid ratio of 1g:10mL. The positive electrode material fell off the aluminum foil, dried at 80°C for 12 hours, and ground to obtain the cathode powder to be treated.
[0047] Take 10g of the cathode powder obtained by the above treatment and 993.75mL of deionized water and put them into a three-necked flask and mix them evenly, add 6.25mL of a dilute sulfuric acid solution with a concentration of 4M, then pass air micro-nano bubbles to react fully, and filter to obtain lithium-rich leachate, iron phosphate and carbon slag; the gas flow rate is 100mL / min, the temperature is room temperature, the leaching time is 60min, the total volume of the leachate is 1L, and the air micro-nano bubbles are generated by a micro-nano bubble generator (the gas source is air, the air flow rate of the micro-nano bubble generator is 80-120mL, the power is 380W, and the diameter of the generated micro-nano bubbles is 10-130nm). The leachate is measured by an inductively coupled plasma emission spectrometer (ICP-OES) to obtain the metal ion content, and the recovery of lithium and iron obtained by the aqua regia digestion method (National Environmental Protection Standard of the People's Republic of China, HJ 803-2016) is used as a standard, and the recovery rate of lithium is calculated to be 93.4%, and the recovery rate of iron is 8.8%, as shown in Table 1.
[0048] Example 5
[0049] The waste lithium iron phosphate battery was immersed in a NaCl solution with a mass fraction of 8% and discharged until the voltage was below 0.2V, which took about 48 hours. The positive electrode material was disassembled and ultrasonicated (40kHz, 500W) in a NaOH solution with a concentration of 0.3M for 20 minutes, wherein the positive electrode material and the NaOH solution were added in a solid-liquid ratio of 1g:10mL. The positive electrode material fell off the aluminum foil, dried at 80°C for 12 hours, and ground to obtain the cathode powder to be treated.
[0050] Take 10g of the cathode powder obtained by the above treatment and 993.75mL of deionized water and put them into a three-necked flask and mix them evenly, add 6.25mL of a dilute sulfuric acid solution with a concentration of 4M, then pass oxygen micro-nano bubbles for sufficient reaction, and filter to obtain lithium-rich leachate, iron phosphate and carbon slag; the gas flow rate is 100mL / min, the temperature is room temperature, the leaching time is 30min, the total volume of the leachate is 1L, and the oxygen micro-nano bubbles are generated by connecting the oxygen bottle to the micro-nano bubble generator, the air intake flow rate of the micro-nano bubble generator is 80-120mL, the power is 380W, and the diameter of the generated micro-nano bubbles is 10-130nm. The metal ion content of the leachate is measured by inductively coupled plasma emission spectrometer (ICP-OES), and the recovery of lithium and iron obtained by the aqua regia digestion method (National Environmental Protection Standard of the People's Republic of China, HJ 803-2016) is used as the standard, and the recovery rate of lithium is calculated to be 95%, and the recovery rate of iron is 7.2%, as shown in Table 1.
[0051] Table 1 Lithium and iron leaching rates under different conditions
[0052] Serial number Bubble Type Sulfuric acid concentration mol / L Solid-liquid ratio g / L Time min Lithium leaching rate % Iron leaching rate % Example 1 ozone 0.025 10 30 100 0.11 Example 2 ozone 0.04 10 30 100 12 Example 3 ozone 0.01 5 30 100 0.68 Example 4 Air 0.025 10 60 93.4 8.8 Example 5 oxygen 0.025 10 30 95 7.2
[0053] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for selectively leaching lithium from waste lithium iron phosphate batteries, characterized in that The steps include: (1) discharging the waste lithium iron phosphate battery in salt water, crushing and disassembling the battery to obtain lithium iron phosphate material, and separating the positive electrode material; placing the obtained positive electrode material in an alkaline solution for ultrasonication, separation, and drying to obtain a cathode material to be treated; (2) placing the cathode material obtained in step (1) in an acid solution, leaching with gas micro-nano bubbles, and filtering to obtain a lithium-rich leaching solution.
2. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The salt water in step (1) is a NaCl solution with a concentration of 5 to 10% by mass; The alkaline solution described in step (1) is a NaOH solution with a concentration of 0.2 to 0.5 M.
3. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 2, characterized in that: The salt water in step (1) is a NaCl solution with a concentration of 8% by mass; The alkaline solution described in step (1) is a NaOH solution with a concentration of 0.3M.
4. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The amount of the alkaline solution in step (1) is calculated based on the ratio of positive electrode material to alkaline solution of 1 g: 5 to 15 mL.
5. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The degree of discharge in step (1) is to discharge to below 0.2V; The ultrasonic conditions in step (1) are: 35-45 kHz, 400-600 W; The ultrasonic time in step (1) is 10 to 30 minutes; The drying conditions described in step (1) are drying at 60° C. to 120° C. for 6 to 24 hours.
6. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The acid in step (2) is at least one of H2SO4, HCl, citric acid, phosphoric acid, oxalic acid and acetic acid; The gas described in step (2) is at least one of O3, O2 and air.
7. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The concentration of the acid solution in step (2) is 0.01 to 0.04 mol / L; The amount of the acid solution in step (2) is calculated based on a ratio of 5 to 100 g of cathode material to acid solution: 1 L.
8. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 7, characterized in that: The concentration of the acid solution in step (2) is 0.01 to 0.025 mol / L; The amount of the acid solution in step (2) is calculated based on a ratio of 5 to 10 g of cathode material to acid solution: 1 L.
9. The method for selectively leaching lithium from waste lithium iron phosphate batteries according to claim 1, characterized in that: The diameter of the micro-nano bubbles in step (2) is 10-130 nm; The leaching time in step (2) is 10 to 150 minutes; The leaching temperature in step (2) is 10-80°C.
10. Use of the method for selectively leaching lithium from waste lithium iron phosphate batteries according to any one of claims 1 to 9 in lithium recovery.
Citation Information
Cited By
Method for recycling valuable metal in retired lithium ion battery by using leaching solvent
CN121161017A